Expression of CXCR4, VLA-1, LFA-3 and transducer of ERB in G-CSF-mobilised progenitor cells in acute myocardial infarction - Stein, Andreas; Zohlnhöfer, Dietlind; Pogatsa-Murray, Gisela; Wedel, Jasper von; Steppich, Birgit A.; Schömig, Albert; Kastrati, Adnan; Ott, Ilka (Thrombosis and Haemostasis, 2010)
G-CSF induced mobilisation of progenitor cells is a multistep processes involving chemokines, growth factors, matrix-degrading enzymes, and cell adhesive interactions mediated by specific receptors on haematopoietic cells. This study’s aim was to investigate progenitor cells mobilised during myocardial infarction after treatment with granulocyte-stimulating factor (G-CSF). In the randomised, double-blind, placebo-controlled REVIVAL-2 study, 114 patients with acute myocardial infarction were included. Five days after successful percutaneous coronary intervention patients received either 10 μg/kg G-CSF (n=56) or placebo (n=58) subcutaneously for five days. Venous blood samples were analysed on day(s) 1, 3, 5 and 7 after therapy, and progenitor cell mobilisation and surface expression of VLA-4, LFA-1 and CXCR-4 was measured on circulating progenitor cells using flow cytometry. G-CSF induced a significant increase in circulating progenitor cells (72 ± 20 cells/μl vs. 4.5 ± 0.8 cells/μl, p<0.05). Surface expression of LFA-1, VLA-4 and CXCR4 on progenitor cells was decreased by 44%, 49% and 60% after G-CSF as compared to placebo (p<0.05). In accordance, mRNA expression of CXCR4 was reduced. Moreover, anti-proliferative transducer of ERB (TOB) mRNA was decreased, suggesting an increased proliferative potential of the mobilised progenitor cells. Decreased expression of adhesion and chemokine receptors on G-CSF mobilised progenitor cells in acute myocardial infarction may alter the homing capacity of circulating cells to the myocardium.
Keywords: G-CSF; progenitor cells; acute myocardial infarction; adhesion receptors